PERSEPSI GURU TENTANG PERAN KOMITE SEKOLAH SEBAGAI BADAN PENGONTROL DI SEKOLAH DASAR (SD) KECAMATAN BUKIT SUNDI KABUPATEN SOLOK - ERIL RINALDO (Universitas Negeri Padang, 2016)
The purpose of this research is for getting information about teachers’s perception of the role school comitte as a controller at elementary school Kecamatan Bukit Sundi Kabupaten Solok. The population are 211 people and sample are 58 people, determined by using Arikuntos’s sampling technique. Instrumen that used is questionnaire scale likert model. Data analysis by using the formula average. The results showed the overall the role of the school comitte as a controller at elementary school Kecamatan Bukit Sundi Kabupaten Solok enough categories with an average score of 3.1.